2018
DOI: 10.1016/j.rboe.2018.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic rotator cuff repair: single-row vs. double-row – clinical results after one to four years

Abstract: ObjectiveEvaluate and compare the results of single-row (SR) vs. double-row (DR) arthroscopic rotator cuff repair.MethodsFrom December 2009 to May 2013, 115 arthroscopic rotator cuff repairs were performed using suture anchors. After applying the exclusion criteria, there were 75 patients (79 shoulders) to be evaluated, retrospectively, of whom 53 (56 shoulders) attended re-evaluation. The patients were divided into two groups: SR with 29 shoulders, and DR) with 27 shoulders. The scoring systems for clinical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 24 publications
2
22
0
5
Order By: Relevance
“…Nicholas et al [19] 2016 II 49 SR = DR -All size Transosseous equivalent SR: single row repair; DR, double row repair; MRA: Magnetic Resonance arthrography; PRP: platelet-rich plasma fibrin membrane. [20] 2012 108 1980-2012 -Roth et al [21] 2014 10(7 level I studies and 3 level 2 studies) 2007-2013 SR = DR Ying et al [22] 2015 11(7 level I studies and 4 level 2 studies) 2007-2012 SR < DR; in large tears Sobhy et al [23] [7][8][9] reported better clinical outcomes of DR compared to SR, whereas some [10][11][12][13] described no difference of clinical outcomes between SR and DR. The purpose of this article was to review the current evidence regarding outcomes of DR.…”
Section: Radiological Assessment Tear Size Dr Techniques Othersmentioning
confidence: 99%
“…Nicholas et al [19] 2016 II 49 SR = DR -All size Transosseous equivalent SR: single row repair; DR, double row repair; MRA: Magnetic Resonance arthrography; PRP: platelet-rich plasma fibrin membrane. [20] 2012 108 1980-2012 -Roth et al [21] 2014 10(7 level I studies and 3 level 2 studies) 2007-2013 SR = DR Ying et al [22] 2015 11(7 level I studies and 4 level 2 studies) 2007-2012 SR < DR; in large tears Sobhy et al [23] [7][8][9] reported better clinical outcomes of DR compared to SR, whereas some [10][11][12][13] described no difference of clinical outcomes between SR and DR. The purpose of this article was to review the current evidence regarding outcomes of DR.…”
Section: Radiological Assessment Tear Size Dr Techniques Othersmentioning
confidence: 99%
“…Rotator cuff (RC) rupture is one of the most common causes of shoulder pain and disability (1). Although most ruptures are treated conservatively, many methods (especially arthroscopic) for tears requiring surgical intervention have been described in the last two decades.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous techniques have been published and used to treat and repair these tears; these include single- or double-row fixations, sometimes using auto- or allograft for irreparable tears, showing very promising results. 2 Although no significant clinical differences between single- and double-row techniques were shown in most recent studies, 3 , 4 controversy still exists on the treatment of massive rotator cuff tears. Thorsness and Romeo 2 found that superior capsular reconstruction are the best solution for irreparable cuff tears.…”
mentioning
confidence: 99%